The Investigation of Hippocampus-Dependent Cognitive Decline Induced by Anesthesia/Surgery in Mice Through Integrated Behavioral Z-Scoring - Meng, Bo; Li, Xiaoyu; Lu, Bo; Liu, Rongjun; Yuan, Hui; Zhai, Xiaojie; Qin, Jinling; Chen, Zhang; Zheng, Jinwei; Chen, Junping (Frontiers in Behavioral Neuroscience, 2020)
Objective Patients undergoing major surgeries may experience certain cognitive decline, which is known as postoperative delirium (POD) or postoperative cognitive dysfunction (POCD). We employed integrated behavioral Z-scoring introduced by Guilloux et al. (2011) to investigate the effects of fracture fixation under anesthesia on hippocampus-dependent memory in mice. Methods ICR mice (12–14 months) underwent stabilized tibial fracture operation under sevoflurane anesthesia. They were subjected to a battery of successive hippocampus-dependent tests following surgery, including open field test (OF), novel object recognition (NOR), fear conditioning test (FC), and Morris water maze (MWM). The integrated behavioral Z-scoring was applied to assess the hippocampus-dependent memory after anesthesia/surgery, and the association between the integrated behavioral Z-scores and hippocampal pro-inflammatory cytokines was explored. Results Mice after anesthesia/surgery were found to have impaired hippocampus-dependent memory in NOR, FC, and MWM but with different degrees in these aspects as represented by P-value and effect size. The integrated memory Z-scores based on principal parameters of the above three tests can reduced the variability and increase the comprehensiveness of behavioral results. However, we found no statistic associations between hippocampal pro-inflammatory cytokines and the integrated Z-scores, as the elevated cytokines quickly return to normal on postoperative day 3 and/or day 7. Conclusion The integrated Z-score methodology could facilitate the interpretation of the anesthesia/surgery induced cognitive decline in mice and robustly quantify the behavioral phenotyping of hippocampus-dependent memory.